Pseudomonas protegens ML15 and Trichoderma koningiopsis Tr21 co-culture: A potent strategy for suppressing Fusarium cerealis infections in wheat through augmented antifungal metabolite production - Nur Ajijah; Angelika Fiodor; Krzysztof Kazimierczuk; Monika Urbaniak; Elsie Enow; Robert Stasiuk; Lukasz Stepien; Lukasz Dziewit; Kumar Pranaw (Biological Control)
Wheat (Triticum aestivum L.), a staple grain consumed worldwide, is heavily affected by Fusarium species, which cause harmful diseases that threaten its production. The present study was conducted to investigate the biocontrol activity of monocultures of Pseudomonas protegens ML15 and Trichoderma koningiopsis Tr21 as well as their co-culture, as a sustainable strategy to combat Fusarium cerealis. The cell-free supernatant and cell-free extract of co-culture demonstrated increased inhibitory effects against F. cerealis, compared to the monocultures. GC-MS analysis revealed that cell-free extract of P. protegens ML15, T. koningiopsis Tr21, and co-culture contained different bioactive metabolites. Pyrrolo[1,2-a]pyrazine-1,4-dione derivatives were major compounds in the cell-free extract of co-culture. Further analysis using NMR and HPLC, revealed that co-culture produced higher concentrations of pyoluteorin, 2,4-diacetylphloroglucinol, and 2,4-di-tert-butylphenol, compared to their respective monocultures. In vivo plant experiments indicated that co-culture treatment reduced F. cerealis infection and improved wheat development. Our findings highlight the exciting potential of co-culturing P. protegens ML15 and T. koningiopsis Tr21 as a formidable biocontrol duo, particularly effective against notorious fungal plant pathogens like Fusarium. This innovative approach holds promise for revolutionizing agricultural practices, offering sustainable solutions to combat crop diseases, and ensuring global food security.